2017
DOI: 10.3389/fendo.2017.00335
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hypothyroidism and Non-Alcoholic Fatty Liver Disease: A Systematic Review and Meta-analysis

Abstract: BackgroundPrevious studies propose that hypothyroidism might play a crucial role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD), but findings from published studies on the relationship between hypothyroidism and NAFLD are still controversial. Our study aimed to make a comprehensive evaluation of the relationship between hypothyroidism and NAFLD through a meta-analysis.MethodsPubMed, China Dissertation Database, and EMBASE databases were searched to find observational studies assessing the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 65 publications
(51 reference statements)
1
82
0
3
Order By: Relevance
“…A recent meta-analysis provides strong epidemiological evidence for the relationship between hypothyroidism and NAFLD. Both patients with subclinical and overt hypothyroidism are at major risk for NAFLD than euthyroid subjects [103].…”
Section: New and Alternative Mechanismsmentioning
confidence: 99%
“…A recent meta-analysis provides strong epidemiological evidence for the relationship between hypothyroidism and NAFLD. Both patients with subclinical and overt hypothyroidism are at major risk for NAFLD than euthyroid subjects [103].…”
Section: New and Alternative Mechanismsmentioning
confidence: 99%
“…Our meta-analysis exploring the association between variably defined primary hypothyroidism and the risk of NAFLD is the largest and most comprehensive assessment to date. Two previous smaller meta-analyses have yielded controversial findings (25,26]. One meta-analytic study of nine studies (involving a total of *32,000 subjects) showed that patients with NAFLD had no significant differences in serum thyroid hormone levels compared with control individuals and that there was no significant association between variably defined primary hypothyroidism and NAFLD (random-effects OR 1.21 [CI 0.91-1.61]; I 2 = 72%) (25).…”
Section: Figmentioning
confidence: 99%
“…In addition, they did not include studies performed in adolescents (23,24), and crosssectional or longitudinal studies published in adults from 2016 to 2018 (20)(21)(22). Conversely, in the other published meta-analysis of 13 cross-sectional and longitudinal studies (involving a total of *41,000 subjects), He et al reported a significant association between variably defined primary hypothyroidism and the risk of NAFLD (random-effects OR 1.52 [CI 1.24-1.87]; I 2 = 75.1%) (26). Compared with our meta-analysis, these authors have included eleven studies identical to those included in our meta-analysis (10)(11)(12)(13)(15)(16)(17)19,20,23,24), but also an unpublished M.D.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations